Nilai-nilai Kearifan Lokal Tradisi Nyadran Sebagai Sumber Belajar IPS - Ibnu Mustopo Jati (FKIP, Universitas Palangka Raya, 2022)
There are concerns that the existence of globalization can make students more interested in adopting foreign cultures than their native cultures. Incorporating local wisdom into learning is the best way to overcome this. Because the Nydran tradition is one of the local Wisdom with Indonesian cultural values, this local wisdom can be used as an alternative source for social studies learning so that learning is more meaningful. This study aims to: 1) describe the history, form, and meaning of the Nydran tradition, 2) describe the values ​​inherent in the Nydran tradition, and 3) describe the value of the Nydran tradition as an alternative social studies learning resource. This study uses a literature study research method. The results of this study are the history of the Nydran tradition, starting from Hindu-Buddhist, then acculturated with Islam to be used as a medium da’wah. The meaning and form of the Nydran tradition are different in each region, but has the same goal of expressing gratitude to God and ancestors. Nydran's tradition values, namely: social, religious, cultural, and educational values. These values ​​are relevant and by the objectives of social studies learning, which is to make students as citizens who know their original culture.